Smart Cards, Smarter Policy: Medical Records, Privacy, and Health Care Reform - Alpert, Sheri (The Hastings Center report, 1993)
Current law does not adequately protect patients' privacy or their medical records. Proposals to computerize these records could further erode confidentiality unless new federal laws are enacted.